2017
DOI: 10.1016/j.nicl.2016.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of white matter structural networks in patients with non-neuropsychiatric systemic lupus erythematosus identified by probabilistic tractography and connectivity-based analyses

Abstract: PurposeSystemic lupus erythematosus (SLE) is a chronic inflammatory female-predominant autoimmune disease that can affect the central nervous system and exhibit neuropsychiatric symptoms. In SLE patients without neuropsychiatric symptoms (non-NPSLE), recent diffusion tensor imaging studies showed white matter abnormalities in their brains. The present study investigated the entire brain white matter structural connectivity in non-NPSLE patients by using probabilistic tractography and connectivity-based analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
(104 reference statements)
5
10
0
Order By: Relevance
“…Additional longitudinal studies are needed to verify this prediction. While several studies have reported WM alterations in NPSLE compared with HC subjects in segments of the CC, the forceps, anterior corona radiata, thalamus, and parietal and frontal lobes (33-36) and overall diminished volume of the CC (34, 37), our results support the growing body of literature demonstrating significant WM abnormalities in SLE subjects without acute neuropsychiatric manifestations (38)(39)(40)(41)(42). Most of these studies in SLE subjects without neuropsychiatric manifestations failed to demonstrate significant correlations between diminished WM integrity and cognition.…”
Section: Table 4 Brain Regions With Significant Differences In Fa Besupporting
confidence: 87%
“…Additional longitudinal studies are needed to verify this prediction. While several studies have reported WM alterations in NPSLE compared with HC subjects in segments of the CC, the forceps, anterior corona radiata, thalamus, and parietal and frontal lobes (33-36) and overall diminished volume of the CC (34, 37), our results support the growing body of literature demonstrating significant WM abnormalities in SLE subjects without acute neuropsychiatric manifestations (38)(39)(40)(41)(42). Most of these studies in SLE subjects without neuropsychiatric manifestations failed to demonstrate significant correlations between diminished WM integrity and cognition.…”
Section: Table 4 Brain Regions With Significant Differences In Fa Besupporting
confidence: 87%
“…A study in 52 normal individuals at the beginning of the 8th decade of life observed that despite WMH having similar effects on tract infrastructure, whether they be intersecting or nearby, differences in tract water diffusion properties around WMH suggest that tract degeneration may propagate along the white matter tract for intersecting WMH, while in some areas of the brain there is a larger and more localized accumulation of axonal damage in tract tissue nearby a non-connected WMH. 47 This study also complements findings by other studies in smaller SLE samples, which found altered structural network parameters in SLE patients 13,14 compared to controls, with only few differences in functional hub measures. 14…”
Section: Discussionsupporting
confidence: 88%
“…12 Another study found that brain connectivity networks in SLE patients had decreased efficiency and increased characteristic path length compared to healthy controls. 13 Complementary to the previously mentioned study, 12 regional network degree and nodal efficiency in frontal, occipital and cingulum regions negatively correlated with disease activity in this smaller SLE cohort. 13 Another study also found abnormal global efficiency and network path length in SLE patients compared to controls despite similar functional hub connectivity measurements.…”
Section: Introductionsupporting
confidence: 73%
“…Abnormalities in NPSLE likely represent demyelination and/or altered network connectivity not seen with conventional MRI sequences . Using brain connectivity analysis of diffusion MRI data, reduced nodal efficiency in the brain network was observed in patients with NPSLE, compared to controls .…”
Section: Current Status Of Npslementioning
confidence: 96%
“…Preliminary studies in SLE suggest compensatory adaptation of neuronal function through recruitment of additional cortical pathways. These compensatory responses maintain cognitive function in the short term but may eventually be overcome and manifest as overt cognitive impairment . Even SLE patients without clinical NP disease have abnormal fMRI resting‐state brain intrinsic connectivity , raising the possibility of preclinical detection .…”
Section: Current Status Of Npslementioning
confidence: 99%